High capacity novel protocols for common destination wireless relay systems - Atan, Sinan; Aygölü, Ümit (IEEE, 2015)
In this paper, three novel protocols, based on automatic repeat request (ARQ), are proposed for common destination relayed wireless communication systems on the behalf of rate and reliability. Then these protocols are compared for goodput, normalized goodput, energy efficiency and reliability merits.